PENGARUH KOMPETENSI SPRITUALITAS GURU PAI TERHADAP PEMBENTUKAN MORAL KEAGAMAAN PESERTA DIDIK DI SMA SUNGAI APIT KABUPATEN SIAK - Saiful Anam; Muhammad Fitriadi; Granita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the influence of Islamic Religious Education (PAI) teachers’ spiritual competence on the formation of students’ religious morals at a senior high school in Sungai Apit District, Siak Regency. Teachers’ spiritual competence includes faith, piety, exemplary behavior, discipline, and consistency in worship, while students’ religious morals encompass discipline, obedience in worship, good character, responsibility, and daily behavior. This study uses a quantitative approach with an ex post facto method and associative research type. The population consists of all students, with a sample of 40 selected through proportional random sampling. Data were collected using a four-point Likert scale questionnaire and analyzed using normality and linearity tests, simple regression, t-test, and determination test (R²) with SPSS. The results show that PAI teachers’ spiritual competence has a significant effect on the formation of students’ religious morals. The R² value of 0.514 indicates that 51.4% of the variation in students’ religious morals can be explained by teachers’ competence. These findings emphasize the importance of strengthening teachers’ spiritual competence through training, character development, and routine supervision to cultivate students with noble character and strong religiosity.